Impact of body mass index on outcome in stroke patients treated with intravenous thrombolysis. (1st August 2016) - Gensicke, H.; Wicht, A.; Bill, O.; Zini, A.; Costa, P.; Kägi, G.; Stark, R.; Seiffge, D. J.; Traenka, C.; Peters, N.; Bonati, L. H.; Giovannini, G.; et al.
Abstract : Background and purpose: The impact of body mass index (BMI) on outcome in stroke patients treated with intravenous thrombolysis (IVT) was investigated. Methods: In a multicentre IVT‐register‐based observational study, BMI with (i) poor 3‐month outcome (i.e. modified Rankin Scale scores 3–6), (ii) death and (iii) symptomatic intracranial haemorrhage (sICH) based on criteria of the ECASS II trial was compared. BMI was used as a continuous and categorical variable distinguishing normal weight (reference group 18.5–24.9 kg/m 2 ) from underweight (<18.5 kg/m 2 ), overweight (25–29.9 kg/m 2 ) and obese (≥30 kg/m 2 ) patients. Univariable and multivariable regression analyses with adjustments for age and stroke severity were done and odds ratios with 95% confidence intervals [OR (95% CI)] were calculated. Results: Of 1798 patients, 730 (40.6%) were normal weight, 55 (3.1%) were underweight, 717 (39.9%) overweight and 295 (16.4%) obese. Poor outcome occurred in 38.1% of normal weight patients and did not differ significantly from underweight (45.5%), overweight (36.1%) and obese (32.5%) patients. The same was true for death (9.5% vs. 14.5%, 9.6% and 7.5%) and sICH (3.9% vs. 5.5%, 4.3%, 2.7%). Neither in univariable nor in multivariable analyses did the risks of poor outcome, death or sICH differ significantly between BMI groups. BMI as a continuous variable was not associated with poor outcome, death or sICH in unadjusted [OR (95% CI) 0.99 (0.97–1.01), 0.98 (0.95–1.02), 0.98 (0.94–1.04)] or adjusted analyses [OR (95% CI) 1.01 (0.98–1.03), 0.99 (0.95–1.05), 1.01 (0.97–1.05)], respectively. Conclusion: In this largest study to date, investigating the impact of BMI in IVT‐treated stroke patients, BMI had no prognostic meaning with regard to 3‐month functional outcome, death or occurrence of sICH.